Congenital pouch colon: Our experience with coloplasty - Sudhir Singh; J D Rawat; Piyush Kumar (Wolters Kluwer Medknow Publications, 2018)
Background: Congenital pouch colon (CPC) or congenital short colon is an entity found mainly in Indian subcontinent. In CPC, colon is replaced with partially or completely abnormal pouch connected to the genitourinary tract by a fistula (colovesical). Management protocol is different in different institute. In this article, we are sharing our three stage standard management approach; principle and technique of coloplasty in cases in which colon length is not adequate for pull through and their follow-up. This study aims to show the result of coloplasty in complete CPC. Materials and Methods: This is retrospective observational study, of 5 years duration. The medical record of these patients was reviewed for demographic information, clinical features, investigations performed, operative notes, post-operative events and the outcome of surgery. Results: Total of 626 ARM cases were managed in 5 years duration in which 64 were of pouch colon. The age of presentation was 1-15 days. In fifty patients who completed their, all stage in that 34 patients were in which coloplasty were done in rest of 16 cases excision of CPC and colonic pull through done in view of adequate colonic length (type III and IV) for pull through. In 34 patient in which coloplasty were done showed satisfactory cosmetic and functional out came after stoma closer in follow-up. Conclusions: Properly created coloplasty and three stage procedure for complete pouch colon give better result and less complications. Excision of pouch is not requiring in all cases of CPC.